(untitled) (Raparin Journal of Humanities (RJH), 2022)
The study aimed to determine and display the level of applying modern technologies in news programs and their impacts on journalist performance. This study depended on descriptive study by using survey method. The study was conducted on(80) journalist in Rudaw satellite channel through selecting conditional sampling. The researcher used questionary tools and observation methods in data collections. The present study concluded that, the most research samples agreed that using of modern techniques ,have many important in producing news programs . Also, the use of modern techniques and variety of news content are considered the most important types to attractive audiences. This research confirmed that using the modern techniques , has many impact of the journalist performance. In which it becomes giving the loyalty and Famous. Also their rolls in presenting of news content ,that’s lead to invention and apply their skills within modern techniques.